ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERENCANAAN OPTIMAL RUMAH SARANG BURUNG WALET DI KALIMANTAN BARAT - Kuang, Sun; Sahputra, Rachmat; Tawil, Hamzah (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2024)
This study analyzed the factors influencing the optimal planning of swallow nest houses in the Siantan region of West Kalimantan, focusing on one semi-traditional type house. The study identified strengths, weaknesses, opportunities and threats (SWOT) through qualitative and descriptive analysis. The results showed that house size, fluctuations in the number of swallows, and fluctuations in market prices had a significant impact on income. Although initial investment and environmental conditions are stable, expansion of house size, technological improvements, and monitoring of the swallow population are key factors to optimize production and income. This study highlights the need for long-term planning that considers price fluctuations, changing environmental conditions, and sustainability principles to achieve business stability and manage risks. This study provides recommendations for swallow nest house owners to improve optimal planning and income, such as expanding house size, improving technology, product diversification, collaboration with stakeholders, monitoring external conditions, and risk management. This research is expected to assist in business strategy formulation, human resource training, and innovation adoption in the swallow nest industry.